Strong isoprene emission response to temperature in tundra vegetation - Seco, Roger; Holst, Thomas; Davie-Martin, Cleo L.; Simin, Tihomir; Guenther, Alex; Pirk, Norbert; Rinne, Janne; Rinnan, Riikka (Proceedings of the National Academy of Sciences, 2022)
Emissions of biogenic volatile organic compounds (BVOCs) are a crucial component of biosphere-atmosphere interactions. In northern latitudes, climate change is amplified by feedback processes in which BVOCs have a recognized, yet poorly quantified role, mainly due to a lack of measurements and concomitant modeling gaps. Hence, current Earth system models mostly rely on temperature responses measured on vegetation from lower latitudes, rendering their predictions highly uncertain. Here, we show how tundra isoprene emissions respond vigorously to temperature increases, compared to model results. Our unique dataset of direct eddy covariance ecosystem-level isoprene measurements in two contrasting ecosystems exhibited Q10 (the factor by which the emission rate increases with a 10 °C rise in temperature) temperature coefficients of up to 20.8, that is, 3.5 times the Q10 of 5.9 derived from the equivalent model calculations. Crude estimates using the observed temperature responses indicate that tundra vegetation could enhance their isoprene emissions by up to 41% (87%)-that is, 46% (55%) more than estimated by models-with a 2 °C (4 °C) warming. Our results demonstrate that tundra vegetation possesses the potential to substantially boost its isoprene emissions in response to future rising temperatures, at rates that exceed the current Earth system model predictions. We are grateful to ICOS Sweden, the Abisko Scientific Research Station (ANS), and the Finse Alpine Research Centre for providing excellent logistics for the work, and we are grateful in particular to Mikkel Sillesen Matzen, John Hulth, Andreas Westergaard-Nielsen, and Rune Maigaard for field assistance and to Jutta Holst for assistance with data. High-frequency wind data from Abisko were provided by ICOS Sweden, which has been cofinanced by the Swedish Research Council (grant 2019-00205); Abisko-Stordalen has been hosted by ANS and SITES "Swedish Infrastructure for Ecosystem Sciences" (cofinanced by the Swedish Research Council). This research has been ...